2014
DOI: 10.1038/ejcn.2014.133
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of vitamin D status in subjects that consume a vitamin D supplement

Abstract: Vitamin D supplementation was the most significant positive predictor of vitamin D status. Collectively, these data point to the practicality of utilizing vitamin D supplements to reduce hypovitaminosis D in adults throughout the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…This is supported by Levy et al who found that BMI was the second largest (and the largest negative) determinant of vitamin D status in persons consuming a vitamin D supplement [20]. Persons with a high BMI generally have a higher content of body fat that may both serve as a storage reservoir but is also extremely slow to release vitamin D [20].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This is supported by Levy et al who found that BMI was the second largest (and the largest negative) determinant of vitamin D status in persons consuming a vitamin D supplement [20]. Persons with a high BMI generally have a higher content of body fat that may both serve as a storage reservoir but is also extremely slow to release vitamin D [20].…”
Section: Discussionmentioning
confidence: 79%
“…Persons with a high BMI generally have a higher content of body fat that may both serve as a storage reservoir but is also extremely slow to release vitamin D [20]. Low circulating vitamin D levels in obese persons may therefore result from a dilution effect of vitamin D within the large body mass [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D level of 75 nmol·L –1 may be a more appropriate goal for most people [27, 28]. Among these people, 56.04% had normal levels of vitamin D. The result of ANOVA analysis revealed that there is statistical significant difference between the level of vitamin D among the 3 groups and also demographic and bio-indices: age ( p  = 0.008), insulin ( p  = 0.028), fat percentage ( p  = 0.0002), fat free mass ( p  = 0.0003), RMR ( p  = 0.08), RMR/kg body weight ( p ≤ 0.0001), RMR/BMI ( p ≤ 0.0001), VDR ( p ≤ 0.0001), and PGC ( p ≤ 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…A dose of 800 IU of vitamin D achieved levels of 30 ng/mL at 6 and 12 months. Other studies have shown that vitamin D supplements increase vitamin D levels in both summer and winter, with no seasonal differences [28,29,30]. The strength of the study lies in the homogeneity of the study population, the methodological design, and the genistein dose.…”
Section: Discussionmentioning
confidence: 96%